Unveiling Melanoma: A Deep Dive into Disparities at a Latin-American Cancer Institute - Ziegler-Rodriguez, Gonzalo (2024)
Introduction: The worldwide incidence of melanoma has increased in the last 40 years. Our aim was to describe the clinic-pathological characteristics and outcomes of three cohorts of patients diagnosed with melanoma in a Latin-American cancer institute during the last 20 years. Methods: We evaluated three retrospective patient cohorts diagnosed with melanoma at Instituto Nacional de Enfermedades Neoplasicas (INEN), a public hospital in Lima, Peru, for the years 2005–2006, 2010–2011, and 2017–2018. Survival rate differences were assessed using the Log-rank test. Results: Overall, 584 patients were included (only trunk and extremities); 51% were male, the mean age was 61 (3–97) years, and 48% of patients resided in rural areas. The mean time to diagnosis was 22.6 months, and the mean Breslow thickness was 7.4 mm (T4). Lower extremity was the most common location (72%). A majority of the patients (55%) had metastases at the time of presentation, with 36% in stage III and 19% in stage IV. Cohorts were distributed as 2005–2006 (n = 171), 2010–2011 (n = 223), and 2017–2018 (n = 190). No immunotherapy was used. Cohort C exhibited the most significant increase in stage IV diagnoses (12.3%, 15.7%, 28.4%, respectively; p < 0.01). The median overall survival rates at the three-year follow-up demonstrated a decline over the years for stages II (97%, 98%, 57%, respectively; p < 0.05) and III (66%, 77%, 37%; p < 0.01). Conclusions: There has been a worsening in the incidence of late-stage metastatic melanoma in Peru throughout the years, coupled with a significant decline in overall survival rates. This is underscored by the fact that half of the population lives in regions devoid of oncological access.